PERAN UANG DALAM PENGAMBILAN KEPUTUSAN MANAJERIAL - Rajagukguk, Yosia Suhendri; Remus Silalahi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to examine economic actors’ perspectives on the importance of money in daily interactions and transactions, as well as in managerial decision-making processes. As a medium of exchange, money not only facilitates the exchange of goods and services but also shapes more efficient and structured economic behavior. In the context of modern business, money functions as a planning tool, a basis for investment decision-making, a means of control and evaluation, a determinant of risk, and a source of motivation and incentives. Furthermore, developments in payment technologies have expanded the understanding of the functions of money in economic activities. The findings of this study are expected to contribute to microeconomic literature, particularly in understanding the behavior of economic and managerial actors in utilizing money as a key instrument in daily activities and decision-making.